A Web Scraping of Chemical Compounds with an Anti-Drug Feature Using IoT - Nadia Mahmood Hussien; Yasmin Makki Mohialden (Journal La Multiapp, 2022)
As a result of the COVID-19 epidemic, there has been an increase in the demand for electronic education apps in schools and colleges in recent years. The purpose of this paper is to develop an educational application for chemistry students at different levels of study that will allow them to obtain precise information on chemical substances in a timely and safe manner. This program uses a web scraping technique by applied a RESRful API to extract information from websites, which is then sent to the student's account. Furthermore, due to the use of the Internet of Things, the application has an anti-explosives and narcotics property using (IOT). The application can retrieve and save information entered by the user on chemical compounds with a high level of security. The medication's chemical formula, as well as the covalent and ionic bonding of compounds, can be displayed. It also has a database that lists all of the hazardous substances. If a user enters a dangerous compound containing narcotics more than four times, an alarm message is sent to the administrator via the Internet of Things.